1999
DOI: 10.1002/(sici)1098-2299(199910)48:2<53::aid-ddr2>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolyl-N-substituted amides: A group of effective anti-inflammatory agents with potential for local anesthetic properties. Synthesis, biological evaluation, and a QSAR approach

Abstract: A series of thiazolyl‐N‐substituted amides were synthesized and tested for anti‐inflammatory activity. Their RM values were determined as an expression of their lipophilicity. Theoretical calculation of their lipophilicity, as clog P and log D7.4 was also performed. The effect of the synthesized compounds on inflammation, using the carrageenan‐induced mouse paw edema model was studied. In general, the studied compounds were found to be potent anti‐inflammatory agents (23.2–72.1%). Anti‐inflammatory activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…It corresponds to the penetration of a chemical into the cellular systems and is represented by n‐octanol/water partition coefficient (K ow ). It has been used to quantify as log P as well as log D in order to model A and AI activities . Notably, the D709 descriptor representing the presence of halogen group in the QSAR equation coincided with the SAR findings from our previous results.…”
Section: Resultssupporting
confidence: 77%
“…It corresponds to the penetration of a chemical into the cellular systems and is represented by n‐octanol/water partition coefficient (K ow ). It has been used to quantify as log P as well as log D in order to model A and AI activities . Notably, the D709 descriptor representing the presence of halogen group in the QSAR equation coincided with the SAR findings from our previous results.…”
Section: Resultssupporting
confidence: 77%
“…In eqs 10,15,18,47,48,57, and 58, the activity was shown to have a significant dependence on Hammett's σ constant, which represents the effect of charge-charge or charge-dipole interactions of compounds.…”
Section: Conclusionoverviewmentioning
confidence: 99%
“…•Kuchar and co-workers studied the activity of arylalkanoic acids in vivo in the kaolin-induced rat paw edema assay. They showed that the potency of the compounds correlated with their hydrophobic and electronic properties: •For a group of thiazolyl N-substituted amides tested as anti-inflammatory agents using the carrageenan-induced mouse paw edema assay, a parabolic dependence of activity CPE% on c log D 7.4 and a linear dependence on surface tension were found •For a series of 2-(2-pyridinyl)benzimidazoles, which were synthesized and evaluated for anti-inflammatory activity by the carrageenan-induced rat paw edema assay, a linear equation was derived: Clog P is the calculated lipophilicity of the whole molecule, whereas MR R 1 is the molar refractivity for R 1 substituents.…”
Section: Review Of Nsaid Qsar Studies From the Literaturementioning
confidence: 99%
“…Imines and their derivatives are important intermediates for the synthesis of dyes, fragrances, fungicides, pharmaceuticals and agricultural chemistry [14] . Traditionally, imines are prepared from acid‐catalyzed condensation of aldehyde or ketone with amines.…”
Section: Synthesis Of Iminesmentioning
confidence: 99%